Governance and Ethical Frameworks for AI Integration in Higher Education: Enhancing Personalized Learning and Legal Compliance - Al-Omari, Omaia; Alyousef, Awad; Fati, Suliman; Shannaq, Fatima; Omari, Asem (Journal of Ecohumanism, 2025)
The rise of AI in higher education offers significant opportunities for streamlining learning outcomes, operational efficiency, and even institutional progress. Besides personalized learning systems, the adoption of AI should integrate these ethical, and sometimes even legal, frameworks. The student’s engagement and academic performance can be best improved with adaptive learning technologies and predictive analytics. Also, included in the study are; identification and exploration of limits, such as challenges faced by emerging technologies, meaning that students need to be cautious. Data breaches, biases in algorithms, scarce resources, and resistance to change will work as unique obstacles; hence, suggestions presented will be quite specific to each of these themes. Higher education will undergo transformative changes, traversing from inclusivity and innovation through the mechanisms of stronger governance, capacity building, and international cooperation; with AI, such pathways are possible. Such discoveries underscore the importance of developing interdisciplinary research capable of generating both transparent and effective frameworks. This would ensure that the longer-term impact of AI utilization is harmonized with educational and societal targets.